Impact of Interviewers’ Personal Bias on Hiring of Law Enforcement Applicants - Diffley, Richard W (2020)
Individuals posing a risk to the community who pass preemployment interviews represent a problem for law enforcement departments and their communities. The purpose of this phenomenological study was to explore the shared experiences of participants regarding hiring biases that may exist among individuals tasked with interviewing law enforcement applicants. Argyris’s organizational learning theory provided the framework for the study. Data were collected from semistructured interviews with 4 participants who had experience interviewing applicants for placement in a law enforcement department.Data were analyzed to identify themes.Biases included participants’ interpretation of applicants’ appearance, body language, ability to handle stress/pressure, preparedness for the interview, problem-solving ability, and responses to questions that matched preselected answers applicant interviewers require for scoring purposes.Findings may be used to improve the law enforcement hiring process and to enhance relationships between law enforcement departments and their communities